WEEKLY "TRYZUB" IN THE REFLECTION BEING BANDURA UKRAINIAN FOREIGN PERIOD OF INTERMILITARY DECADE ХХ OF ITEM - Doutchac, V. G. (PRECARPATHIAN BULLETIN OF THE SHEVCHENKO SCIENTIFIC SOCIETY Word, 2021)
The article author makes the analysis of the «TRYZUB» weekly source study character from the point of view of the culture events and problems reflection both with the XXth century between wars period Ukrainian diaspora bandura art reality one’s in Europe. The art cost of the weekly publications about the cobsar art was estimated both with the one’s role in the popularization of the bandura art in the emigrant groups.